DEVELOPMENT OF A SYSTEM OF AUTOMATIC CHANGE OF WORKING MODES OF GROUP CONTROL STATIONS - Ikramovich, Khafizov Islom; Islomovich, Hafizov Xudoyor; Ergashevich, Soibov Johongir (PT. Antis International Publisher, 2025)
Objective: Effective management of multiple devices is crucial in modern industrial enterprises and infrastructures. Automating the start and stop of these devices at specific times enhances energy efficiency, optimizes production processes, and ensures safety. This study aims to develop a system that automates the switching of operating modes in group control stations to regulate device operation according to predefined schedules. Methods: The research involves designing and implementing a system that integrates automation technologies for controlling multiple devices. The system is developed to enable automatic switching of operational modes in group control stations based on preset schedules. Key technical aspects, including hardware configuration and software algorithms, are analyzed to ensure seamless operation and adaptability to various industrial environments. Results: The developed system successfully automates the start and stop functions of multiple devices according to predefined time settings. It enhances energy efficiency by minimizing idle device operation and optimizing production workflows. Additionally, the system improves safety by ensuring that critical processes follow scheduled operations, reducing human intervention and potential operational errors. Novelty: This study introduces an innovative approach to automating group control station operations by integrating time-based scheduling mechanisms. Unlike conventional manual or semi-automatic control methods, this system ensures precise and reliable device management, leading to enhanced efficiency, safety, and sustainability in industrial environments.